Improving forensic mental health care to Indigenous Australians: theorizing the intercultural space. Issue 4 (26th August 2013) - Durey, A.; Wynaden, D.; O'Kane, M.
Accessible summary This paper uses the 'intercultural space' as an educational strategy to prepare nurses to work respectfully with Indigenous patients in a forensic mental health context; offers an educational approach that introduces nurses to Indigenous knowledge, beliefs and values, examines power relations in colonized countries between the dominant white cultural group and the Indigenous population and encourages nurses to critically reflect on their health care practice; and explores the intercultural space as a shared space between cultures fostering open and robust inquiry where neither culture dominates and new positions, representations and understandings can emerge. Abstract Given the disproportionately high number of Indigenous people imprisoned in colonized countries, this paper responds to research from Western Australia on the need to prepare forensic mental health nurses to deliver care to Indigenous patients with mental health disorders. The paper highlights the nexus between theory, research and education that can inform the design and implementation of programmes to help nurses navigate the complex, layered and contested 'intercultural space' and deliver culturally safe care to Indigenous patients. Nurses are encouraged to critically reflect on how beliefs and values underpinning their cultural positioning impact on health care to Indigenous patients. The paper draws on intercultural theory to offer a pedagogical framework that acknowledges the negative impacts of colonization on Indigenous health and well‐being, repositions and revalues Indigenous cultures and knowledges and fosters open and robust inquiry. This approach is seen as a step towards working more effectively in the intercultural space where ultimately binary oppositions that privilege one culture over another and inhibit robust inquiry are avoided, paving the way for new, more inclusive positions, representations and understandings to emerge. While the intercultural space can be a place of struggle, tension and ambiguity, it also offers deep potential for change.